2019
DOI: 10.5194/se-10-871-2019
|View full text |Cite
|
Sign up to set email alerts
|

Induced seismicity in geologic carbon storage

Abstract: Abstract. Geologic carbon storage, as well as other geo-energy applications, such as geothermal energy, seasonal natural gas storage and subsurface energy storage imply fluid injection and/or extraction that causes changes in rock stress field and may induce (micro)seismicity. If felt, seismicity has a negative effect on public perception and may jeopardize wellbore stability and damage infrastructure. Thus, induced earthquakes should be minimized to successfully deploy geo-energies. However, numerous processe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 157 publications
(173 reference statements)
0
35
0
Order By: Relevance
“…Apart from pressure buildup, other triggering mechanisms may induce seismicity (Brown & Ge, 2018;Jiang et al, 2020;Vilarrasa et al, 2019). In particular, buoyancy need to be considered when gases are injected because their density is lower than that of water, which generates buoyancy-induced stress redistribution around the storage formation (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from pressure buildup, other triggering mechanisms may induce seismicity (Brown & Ge, 2018;Jiang et al, 2020;Vilarrasa et al, 2019). In particular, buoyancy need to be considered when gases are injected because their density is lower than that of water, which generates buoyancy-induced stress redistribution around the storage formation (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%
“…The lower the pressure buildup at the caprock, the more the caprock stability and, consequently, the more confidence in the reservoir for storage of carbon dioxide. Vilarrasa et al (2019) studied the stress states in different CO 2 storage sites and concluded that all the sites were far from being critically stressed. Thus, they could sustain a fair amount of pressure buildup due to fluid injection.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the longterm injection scenario of 50 years, maximum pressure change was observed to be more than 11 MPa-a 75% increase from the initial pore pressure of 14.7 MPa. Such a substantial pressure buildup could induce significant seismicity and lead to pore pressure exceeding the minimum principal stress, based on stress data by Vilarrasa et al (2019). Thus, CO 2 injection needs to be carefully planned depending on the initial reservoir conditions and duration of the storage project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CCS should overcome two main hurdles, namely, the risks of induced seismicity (Vilarrasa & Carrera, 2015;Zoback & Gorelick, 2012) and CO 2 leakage (Lewicki et al, 2007;Nordbotten et al, 2008;Romanak et al, 2012), before its widespread deployment takes place. Proper site characterization, monitoring, and pressure management should allow minimizing the risk of perceivable induced seismicity in Gt-scale CO 2 injection (Celia, 2017;Rutqvist et al, 2016;Vilarrasa et al, 2019). The considered storage formations to date include deep saline aquifers, depleted oil and gas fields, and unmineable coal seams in which CO 2 stays in supercritical conditions with a relatively high density but lower than the one of the resident brines (Hitchon et al, 1999).…”
Section: Introductionmentioning
confidence: 99%